AICCRA Mali: Advancing Gender Equity in Climate-Smart Agriculture and Climate Information Services - Diabate, F; Mujawamariya, G; Gondwe, T; Huyer, S. (2025)
AICCRA Mali implemented gender-responsive solutions tailored to the realities of women and youth farmers. Saving-for-Change groups provided women with access to finance, enabling them to invest in innovations and diversify their crops. Pay-as-you-go solar irrigation systems offered affordable access to water, allowing women to grow high-value crops during the dry season and increase their income. These interventions not only addressed technical challenges but also empowered women as decision-makers and leaders in climate-smart agriculture. By reducing labor burdens, improving access to information, and enabling financial autonomy, AICCRA Mali helped women move from the margins to the center of agricultural transformation. Breaking through systemic challenges requires more than innovation, it demands a commitment to equality, inclusion, and the recognition of women’s vital role in building climate resilience.